2020
DOI: 10.17784/mtprehabjournal.2018.16.629
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of adolescents tennis players

Abstract: Background: The anthropometric profile investigation is considered an important parameter to success in sports, however, there is no available study that investigated biometrics parameters in national level teenage players. In this way the aim of this paper was evaluate the anthropometric characteristics of adolescent tennis players by national level. Methods: The anthropometric and body composition evaluation were recognized on 30 adolescents practicing tennis with at least four years. The following parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Based on this background, it is possible to observe that the study of the effect of repeated play on young tennis players is very important, but it is still limited, so much so that, in South America, we did not find research on the subject, we only found some anthropometric characteristics [ 20 , 21 , 22 , 23 , 24 ], cross-sectional evaluations of physical performance [ 7 , 25 ], and mental characteristics [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this background, it is possible to observe that the study of the effect of repeated play on young tennis players is very important, but it is still limited, so much so that, in South America, we did not find research on the subject, we only found some anthropometric characteristics [ 20 , 21 , 22 , 23 , 24 ], cross-sectional evaluations of physical performance [ 7 , 25 ], and mental characteristics [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…En esta misma línea, la mayoría de información disponible que ha estudiado el rendimiento físico en jóvenes tenistas, incorporando distintos indicadores corporales y de aptitud física, es de origen europeo (Berdejo-del-Fresno et al, 2010;Munivrana et al, 2015;Myburgh et al, 2016;Fett et al, 2017;Kramer et al, 2017;Kramer, Huijgen et al, 2016;Kramer, Valente-Dos-Santos et al, 2016;Férnandez-Férnandez et al, 2019;Ulbricht et al, 2015Ulbricht et al, , 2016. Por su parte, en Sudamérica, las indagaciones parecen ser aún incipientes y se han enfocado, principalmente, al estudio de aspectos antropométricos (Rica et al, 2019;Schluga Filho et al, 2016), de la carga externa del juego (Rodríguez y Montoya, 2018) y de la inserción de este deporte con enfoque un socio-cultural (Silva et al, 2017). Junto con ello, en las bases de datos consultadas no se encontraron registros de revisiones bibliográficas o sistemáticas en jóvenes tenistas que aborden de manera integrada aspectos de aptitud física y antropometría.…”
Section: Introductionunclassified